Large gastroduodenal artery pseudoaneurysm and arterioportal fistula in chronic pancreatitis - Caroline J. Cushman; Andrew F. Ibrahim; Thomas Callahan, MD (Radiology Case Reports, 2024)
Visceral artery pseudoaneurysms, particularly those in the gastroduodenal artery (GDA), are rare but serious complications associated with chronic pancreatitis, posing a significant risk of rupture due to their structural fragility. In this case, a 61-year-old male with a history of chronic pancreatitis, alcohol cirrhosis, duodenal ulcer, and COPD presented with persistent abdominal pain and recurrent fevers. Imaging revealed a 7 cm pseudoaneurysm between the GDA and superior mesenteric vein, which was successfully treated with coil embolization. This case highlights the importance of prompt recognition and intervention in managing GDA pseudoaneurysms, particularly when complicated by an arterioportal fistula, and demonstrates the efficacy of endovascular therapy as a minimally invasive treatment option that can significantly improve patient outcomes in complex vascular complications associated with chronic pancreatitis.